MACEDONIAN HIGHER EDUCATION AGAINST THE PRINCIPLES AND GUIDELINES ON EQUITY, INCLUSION AND DIVERSITY: SOCIAL DIMENSION OF BOLOGNA (UKLO Proceedings, 2025)
Social dimension of the Bologna process has continuously attracted attention of high-level discussions in the EU and EHEA and refers to policies and measures that aim to foster equity, inclusion, and diversity within higher education institutions (HEIs). The goal of this paper is to examine the existing national HE policies in the Republic of North Macedonia against the principles and guidelines (P&Gs) for the promotion of equality and inclusiveness in HE developed by the Bologna Follow-up Group (BFUG) and adopted at the Ministerial Conference in Rome in 2020. The research data collection includes the available data from 2020/2021 as a reference year, while the analysis investigates the existing top-level strategy documents, law and bylaws and the country report data from the Bologna Implementation Report 2020. The paper provides an overview of the key findings on how far these policies are aligned with the P&Gs in addressing the social dimension. It also summarizes how the Macedonian HE system with 12 points fare in terms of the 38 basic and 10 scoreboard indicators developed to serve monitoring of these principals. At the end the paper discusses what the key challenges along the way are and provides conclusions and recommendations for improvement.